To what extent is drought‐induced tree mortality a natural phenomenon?. Issue 3 (9th January 2019) - Fensham, Roderick J.; Laffineur, Boris; Allen, Craig D.
Abstract: Aim: Catastrophic forest mortality due to more extreme rainfall deficits and higher temperatures under future climate scenarios has been predicted. The aim of this study is to explore the magnitude of historical drought‐induced tree mortality under pre‐warming conditions. Location: North‐eastern Australia. Time period: 1845–2017. Major taxa studied: Trees. Methods: Field survey, historical analysis and climate analysis. Results: We present evidence of 18%–30% tree mortality from recent droughts across three regions of north‐eastern Australia with rainfall deficits less severe than earlier historical droughts. The corrected temperature record represents modest warming at the stations with long records in the vicinity of the study areas. In terms of rainfall deficit the most severe drought on record occurred in the early 20th century, and historical evidence confirms that this drought and earlier droughts before the advent of pastoralism coincided with substantial tree mortality. Main conclusions: Dramatic declines in woody biomass in response to drought historically occurred more than once a century and are a natural phenomenon in semi‐arid Australia. The magnitude of drought‐induced tree mortality under natural climate fluctuations requires further investigation in other continents. Widespread drought‐induced tree mortality is not just a recent global change phenomenon and has been underestimated as a natural ecological process. However, even more severe forest die‐off events from more extreme hotter droughts are predicted if Earth's warming proceeds as currently projected.